Tubular polyethylene biogas digesters - Eckerwall, Martin; Jansson, Christian; Larsson, Viktor (2015)
The aim of the study was to install a biogas system consisting of three tubular polyethylene biogas digesters at a rural household in Malawi and to evaluate the constructed biogas system with regards to relevant system parameters. The purpose was to evaluate if the technology is a possible solution to reduce deforestation and support Malawi in climate change mitigation and adaptation.